(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Science education, in today’s global education system, encompasses much more than fact-based knowledge. If learners are unable to connect science education to their lives, it becomes meaningless and incomprehensible. Thus, Pakistan, like many other countries worldwide, should adopt a Science Technology Society (STS) approach to science education delivery. The STS approach is aimed at developing scientifically literate citizens capable of making informed choices about socio-scientific issues affecting their lives. The difficulties in adopting this approach in Pakistan stem from four areas that will need to be completely redesigned in accordance with the STS approach. The examination system science textbooks science teacher education programmes and available resources and school facilities are just a few of these areas. A nation’s wealth and prosperity are contingent upon the efficient use of its human and natural resources via industrialisation. Industrialisation requires scientific education and training in technical skills. Science education is critical because it has enormous value in both the student’s personal life and his social life. Students must develop a scientific outlook so that it becomes ingrained in their way of life and culture. The new generation must be equipped with scientific knowledge, a scientific temperament, and a scientific attitude in order to mature and function effectively as citizens in the modern world. All civilised countries promote the study of science and its applications to various fields of activity, believing that the more it accomplishes, the stronger the nation becomes. And this may be why modern education has a strong bias toward science.